2021
DOI: 10.1186/s13019-021-01699-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ventilation strategy during cardiopulmonary bypass on postoperative pulmonary complications after cardiac surgery: a randomized clinical trial

Abstract: Background To determine whether maintaining ventilation during cardiopulmonary bypass (CPB) with a different fraction of inspired oxygen (FiO2) had an impact on the occurrence of postoperative pulmonary complications (PPCs). Methods A total of 413 adult patients undergoing elective cardiac surgery with CPB were randomly assigned into three groups: 138 in the NoV group (received no mechanical ventilation during CPB), 138 in the LOV group (received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For the same reasons, we cannot rule out that different results may have been observed in our study with a more selected "at risk" population. Contrariwise, a recent randomized study showed that the use of ventilation with low FiO 2 (30%) during CPB was associated with less incidence of severe post-operative pulmonary complications than no ventilation (29 vs. 59%) [23]. Differences between studies (including ours) may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 56%
“…For the same reasons, we cannot rule out that different results may have been observed in our study with a more selected "at risk" population. Contrariwise, a recent randomized study showed that the use of ventilation with low FiO 2 (30%) during CPB was associated with less incidence of severe post-operative pulmonary complications than no ventilation (29 vs. 59%) [23]. Differences between studies (including ours) may explain this discrepancy.…”
Section: Discussionmentioning
confidence: 56%
“…Some researchers have confirmed that the use of sedation, and sucralfate, and the appropriate use of antibiotics reduces the risk of respiratory and related pneumonia after patients are transferred to the ICU after surgery, thereby avoiding PMV (17). Other studies have found that the use of invasive and non-invasive sequential mechanical ventilation effectively reduces the time of mechanical ventilation and reduces the incidence of respiratory complications (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Moderate and severe pulmonary problems were 21% less common in the LOV group than in the NoV group in a prior trial (23% vs. 44%, P = 0.001). 15 In order to demonstrate the protective link between ventilation and better postoperative respiratory outcomes in cardiac surgery, the current study included a larger sample size of patients than earlier investigations. While the risk reduction was nearly as good as anticipated, the incidence of events was lower than projected.…”
Section: Discussionmentioning
confidence: 99%